Beyond the 'official' religions: A normative framework for religious recognition in Indonesia - Iman Pasu Purba; Thohir Luth; Tunggul Anshari Setia Negara; Nur Chanifah (Universitas Negeri Yogyakarta, 2026)
The regulation of religious recognition in Indonesia remains problematic to this day. Research on the regulation of religious recognition has not been conducted to date. As a country with diverse religions, Indonesia faces unique challenges in managing religious life for substantive citizenship. The terminology of